Treatment of class III Malocclusion with maxillary expansion and face-mask therapy: A case report - Mansuri, M; Singh, VP (Janaki Medical College Journal of Medical Science, 2014)
The developing class III malocclusion is one of the most challenging problems for the practicing orthodontist to manage clinically. True class III malocclusion is rare in our region as compared to Class II and Class I malocclusion. With adults, orthognathic surgery and dental camouflage is the viable treatment option. A variety of treatment alternatives exists for patients in the developing stages of a Class III malocclusion. In the past much of the therapy has focused on restriction of mandibular growth with chin cups and functional appliances. This is based on the traditional thought that developing Class III malocclusions were the result of prognathic mandible. Recently, however, there has been a growing awareness that the majority of patients with a developing Class III skeletal pattern exhibit a maxillary deficiency with a normal or only slightly prognathic mandible. Therefore, considerable attention has been given to early treatment using maxillary protraction therapy. Using facemask therapy in conjunction with maxillary expansion has been shown in clinical reports to be a successful and predictable treatment option. Treatment should be carried out as early as possible with the aim to prevent it from becoming severe. A case treated with biphasic therapy – orthopaedic appliance followed by fixed orthodontic treatment is presented here. DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11539 Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1):59-63